Determinants of Malaysian Islamic bank deposits performance - Sazana, Ab Rahman (2024)
The lower-than-targeted growth rate in Malaysia’s Islamic banking sector is raising concerns. Islamic banking assets account for only 36.3% of total banking assets, missing the Malaysian government's 2022 target of 40%. Furthermore, Islamic deposits and investment accounts comprised only 41.6% of total bank deposits and savings. The issue is further exacerbated by rapid fluctuations in the growth rate of Islamic bank deposits. Despite these challenges, factors affecting Islamic bank deposits have not been comprehensively studied. Therefore, this research aims to examine the effect of bank-specific factors, macroeconomic factors, and regulatory factors on the performance of Islamic bank deposits. Additionally, business enterprise depositors are measured as a moderating variable in this study. This study employs quantitative approach using secondary data from 16 Islamic banks between 2000 and 2021. The data were collected from Islamic banks’ annual reports, Bank Negara Malaysia, World Bank, Department of Statistics Malaysia, and other specified sources. The data were analyze using panel data regressions. The results indicate that performance of Islamic bank deposits is significantly impacted by bank-specific factors (net profit margin, bank concentration, financing-to-deposit ratio, and bank size) and macroeconomic factors (gross domestic product and inflation). Additionally, the moderating variable of business enterprise depositors only strengthens the relationship between the net profit margin and the performance of Islamic bank deposits. Overall, the findings suggest that bank-specific factors have a more substantial impact on the performance of Islamic bank deposits than macroeconomic and regulatory factors. Therefore, Islamic banks should prioritize bank-specific factors determinants to ensure stability. The efforts shall be performed while also taking macroeconomic factors into meticulous consideration.